Pengaruh Kepemimpinan Transformasional Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Gasol Pertanian Organik - Syahira, Fatma Aisyah; Murniyati (CV Warnak Johanna Nusantara, 2026)
In achieving the targets that have been set, the company must optimize all existing resources while ensuring long-term operational sustainability. In an effort to improve employee performance, the figure of a leader holds a key position because of his ability to motivate and actively involve employees. This study aims to determine and analyze the influence of transformational leadership and work discipline on employee performance. The population in this study were all employees at PT Gasol Pertanian Organik with a total population of 35 employees. The data collection technique used was the survey method by distributing questionnaires, the research used in this study was quantitative statistics, with multiple linear regression analysis methods to examine the influence of these variables. This study also uses analysis methods, namely validity testing, reliability testing, classical assumption testing, and hypothesis testing. Data analysis using SPSS version 25 software, the results of this study indicate that the transformational leadership variable has a positive and significant influence on employee performance of 2.266, and the work discipline variable has a positive and significant influence on employee performance of 2.783. Simultaneous tests show that both independent variables, namely transformational leadership and work discipline, have a positive and significant influence on employee performance with a calculated F value of 85.826.